Theory-of-Change Visuals: Using Diagrams, Metaphors, and Symbols to Communicate Complex Ideas and Get Buy-In - Lambert, Simon; Heimlick, Micheal; Marzano, Mariella; Mark-Shadbolt, Melanie; Smith, Valance (University of Toronto Press Inc. (UTPress), 2025)
Everyone can imagine a situation in which they have put in countless hours of work on a new measurement and evaluation framework and, when it is time to get feedback or present their ideas, they have been met with 1,000-yard stares. Conventional approaches can sometimes struggle to engage stakeholders and convey complex concepts. To address this, authors of this article propose a unique, visually based approach that integrates metaphors and symbols into measurement and evaluation frameworks with goals of getting buy-in, portraying complexity, and making evaluation fun for everyone. Termed theory-of-change visualizations, this methodology emphasizes effective communication and facilitation—two key skills authors argue every evaluator should have. The authors advocate for the use of metaphors and symbols that resonate with stakeholders’ experiences and contexts to anchor frameworks in relatable imagery (such as nature-based symbols or culturally significant metaphors). Illustrated through diverse case studies and practical examples, the approach’s usefulness is demonstrated across various contexts, including in both small and large programs with varied outcomes and dynamics. Insights into selecting appropriate metaphors are provided, considering factors such as program characteristics, local context, and audience preferences. Additionally, potential limitations and challenges, including the requisite time, resources, and stakeholder buy-in, are acknowledged and addressed. Integrating visuals portraying metaphors or symbols into frameworks offers a promising avenue for enhancing engagement, understanding, and buy-in for evaluation. By embracing creativity and inclusivity in evaluation practices, this approach can help navigate the complexities of program evaluation for those not in the field while, at the same time, fostering meaningful dialogue and decision-making.
Keywords: 4404 Development Studies; 4409 Social Work; 4410 Sociology; 44 Human Society; Generic health relevance; 1607 Social Work; Social Sciences Methods; 4404 Development studies; 4409 Social work; 4410 Sociology